2005
DOI: 10.1002/ijc.21066
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MDA-MB-231 cell cycle progression and cell proliferation by C-2-substituted oestradiolmono- andbis-3-O-sulphamates

Abstract: A natural metabolite of oestradiol (E2), 2-methoxyoestradiol (2-MeOE2), exerts both antitumour and antiangiogenic effects. 2-MeOE2 is currently in clinical trials for the treatment of a variety of cancers. We have previously shown that a number of sulphamoylated analogues of 2-MeOE2 possess enhanced potency and bioavailability with respect to 2-MeOE2. In our study, the effects of C-2-substituted E2 derivatives, with sulphamoylation at the C-3 and/or C-17 position, on ERa 2ve MDA-MB-231 breast cancer cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 37 publications
4
30
0
Order By: Relevance
“…It is now known that sulphamoylated derivatives of oestrogens have a superior pharmacokinetic profile and are more resistant to metabolism than their non-sulphamoylated counterparts (Newman et al, 2006). Oestrogen sulphamates, such as oestrone-3-Osulphamate (EMATE) were originally identified as potent STS inhibitors, a property shared with 2-MeOE2bisMATE (Raobaikady et al, 2005). EMATE was not developed for breast cancer therapy as it became evident that oestrogen sulphamates had enhanced oestrogenicity when administered orally to rats (Elger et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now known that sulphamoylated derivatives of oestrogens have a superior pharmacokinetic profile and are more resistant to metabolism than their non-sulphamoylated counterparts (Newman et al, 2006). Oestrogen sulphamates, such as oestrone-3-Osulphamate (EMATE) were originally identified as potent STS inhibitors, a property shared with 2-MeOE2bisMATE (Raobaikady et al, 2005). EMATE was not developed for breast cancer therapy as it became evident that oestrogen sulphamates had enhanced oestrogenicity when administered orally to rats (Elger et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…2-MeOE2bisMATE is thought to act like 2-MeOE2, by binding to the colchicine-binding site on tubulin and altering microtubule stability (MacCarthy-Morrogh et al, 2000;Raobaikady et al, 2005). It induces Bcl-2 phosphorylation and apoptosis in endothelial and cancer epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted with a range of cell lines have shown that STX243 is equipotent to STX140 at inhibiting cell proliferation (Suzuki et al, 2003;Raobaikady et al, 2005). Novel experiments recently conducted by our group have shown that STX243, and also STX140, induce G 2 /M arrest and apoptosis in cells recovered from xenograft tumours .…”
mentioning
confidence: 99%
“…Earlier studies have also shown that STX140 initiates apoptosis, possibly by phosphorylating BCL-2 and activating caspases 3 and 9 (Day et al, 2003;Wood et al, 2004). In vitro STX140 has been shown to inhibit cell proliferation, including preventing the growth of cells that are resistant to conventional chemotherapeutic agents (Suzuki et al, 2003;Raobaikady et al, 2005). In vivo investigations have shown that STX140 is orally effective at inhibiting the growth of both oestrogen-receptor-positive (ER þ ) and oestrogen-receptornegative (ERÀ) tumours (Ireson et al, 2004;Utsumi et al, 2005).…”
mentioning
confidence: 99%
“…The problems of poor bioavailability and rapid metabolism associated with this drug may be overcome by synthesising analogues resistant to conjugative and metabolic inactivation (Leese et al, 2005b). One such compound is 2-methoxyoestradiol-3,17-O,O-bis-sulphamate (STX140), whose potential anti-angiogenic and anti-tumour activities have been well documented (Day et al, 2003;Ho et al, 2003;Newman et al, 2004;Wood et al, 2004;Raobaikady et al, 2005;Utsumi et al, 2005;Leese et al, 2006).…”
mentioning
confidence: 99%